AB0236 Association of lyve-1 protein in exosome with disease activity as a new candidate biomarker for rheumatoid arthritis. (15th June 2017) - Yoo, J; Lee, SK; Lim, M; Sheen, D; Choi, E-H; Kim, SA
Abstract : Background: Exosomes, membrane-bound vesicles of 40–100 nm in diameter, have protein and lipid composition that depends on the cell origin, the state of activation, infection and/or transformation of the parent cells. Those proteins and lipid have a role in mediating inflammatory and autoimmune disease as well. Discovery of inflammatory marker to evaluate appropriate response of treatment could give effective timing to adjust treatment for rheumatoid arthritis patients. Objectives: The aim of the study was to identify protein candidates in exosome being related with other inflammatory parameters. Methods: The study population consisted of 60 RA patients, in which there were 30 patients of clinical remission (CR) group with DAS28-ESR≦2.6 and 30 patients of non-clinical remission (non-CR) group with DAS28-ESR>2.6. By exosome preparation with ExoQuick TM kit and protein identification with tandem mass tags labeling/mass spectrometry between the groups, potent protein markers were selected. Level of the proteins was measured by ELISA. Results: We identified 6 proteins by proteomics approach. Amyloid A (AA) and lymphatic vessel endothelial hyaluronic acid receptor-1 (LYVE-1) was identified with different levels in exosome between CR group and non-CR group. AA levels of both serum and exosome were higher in non-CR group than CR group (p value=0.001). Significant positive correlations were found between exosome AA level and CRP as well as between serum AA level and CRP (ρ=0.614, p value=0.001 and ρ=0.624, p value=0.001). Though LYVE-1 level of serum was not different between non-CR group and CR group, LYVE-1 level of exosome was lower in non-CR group than CR group (p value=0.01). We found positive correlations between serum/exosome of LYVE-1 and CRP in only non-CR group (serum ρ=0.376, p value=0.04; exosome ρ=0.545, p value=0.002). Conclusions: We suggest that LYVE-1 in exosome can be used as an additional marker of disease activity in RA patients and this study provides the evidence about the role of exosome for RA as the carrier of useful marker. References: Mathivanan S, Ji H, Simpson RJ. Exosomes: extracellular organelles important in intercellular communication. J Proteomics. 2010 Sep;73(10):1907–20. Shen C, Sun X-G, Liu N, et al. Increased serum amyloid A and its association with autoantibodies, acute phase reactants and disease activity in patients with rheumatoid arthritis. Mol Med Rep. 2015;11(2):1528–34. Nunomiya K, Shibata Y, Abe S, et al. Relationship between serum level of lymphatic vessel endothelial hyaluronan receptor-1 and prognosis in patients with lung cancer. J Cancer. 2014;5(3):242–7. Disclosure of Interest: None declared